Centres and Peripheries of Psychoanalysis : an Introduction to Psychoanalytic Studies. - Ekins, Richard (Karnac Books, 1994)
This book is designed to meet the needs of students who seek, in one volume, a text which places emphasis upon core concepts and clinical material, but which at the same time reflects the range of applications in therapy ...